The EU Carbon Border Adjustment Mechanism and its Influence on Imports from India - Frank Best (ZBW - Leibniz Information Centre for Economics, 2023)
In its “Fit for 55” program, the European Union (EU) integrates several instruments with the goal of achieving climate neutrality by 2050. One of the cornerstones of the program is the EU Emissions Trading System (EU-ETS), which imposes a levy on CO2 and other greenhouse gas (GHG) emissions, thus internalizing external costs, restoring fair competition, incentivizing sustainable investment and efficiently distributing the remaining greenhouse gas budget through a cost-effective, market-oriented mechanism. This carbon pricing scheme, however, only affects companies which emit GHGs within the EU. Imported products thereby achieve a cost advantage over products produced within the scope of the EU-ETS, leading to competitive pressure on EU-ETS companies and the risk that they might move production facilities outside the scope of the EU-ETS (“carbon leakage”). In order to avoid carbon leakage and encourage cleaner industrial production in partner countries, the EU decided to introduce the Carbon Border Adjustment Mechanism (CBAM) to put a fair price on carbon emissions from the manufacturing of products imported into the EU. The CBAM transitional phase will go into effect on October 1, 2023. Initially, it will only apply to selected industrial products and precursors whose production is particularly carbon intensive and which are deemed to have the highest potential risk of carbon leakage. Once the CBAM is fully active, all importing companies will have to declare the embedded emissions for their products and surrender the corresponding amount of CBAM certificates. It is to be expected that importing companies will strongly rely on their international suppliers to provide information on the embedded emissions. India is both an important trade partner of the EU and, because of its strong reliance on coal power plants, a heavy greenhouse gas emitter both in absolute and relative terms. Importers of products from India into the EU will therefore have to purchase a significant number of carbon allowances under the CBAM regulations. This paper explains the functional mechanism of the CBAM and identifies the product flows from India to the EU for the affected products. It describes the product groups, their importance for Indian companies as well as the future requirements, and is intended to support Indian companies that export to the European Union to prepare for the CBAM requirements both during the transition phase and once the system is fully active. – – Im Rahmen ihres Programms "Fit for 55" integriert die Europäische Union (EU) mehrere Instrumente mit dem Ziel, bis 2050 Klimaneutralität zu erreichen. Einer der Eckpfeiler des Programms ist das EU-Emissionshandelssystem (EU-ETS), das eine Abgabe auf CO2 und andere Treibhausgasemissionen erhebt und somit externe Kosten internalisiert, fairen Wettbewerb wiederherstellt, nachhaltige Investitionen anregt und das verbleibende Treibhausgasbudget durch einen kosteneffizienten, marktorientierten Mechanismus effizient verteilt. Dieses System zur Bepreisung von Kohlenstoffemissionen betrifft jedoch nur Unternehmen, die Treibhausgase innerhalb der EU emittieren. Importierte Produkte erlangen dadurch einen Kostenvorteil gegenüber europäischen Produkten, was zu Wettbewerbsdruck auf EU-Unternehmen führt. Dieser Druck birgt das Risiko der Verlagerung von Produktionsstätten außerhalb des EU-ETS-Bereichs verlagern ("Carbon Leakage"). Um Carbon Leakage zu vermeiden und eine emissionsarme Produktion in Partnerländern zu fördern, beschloss die EU, den Carbon Border Adjustment Mechanism (CBAM) einzuführen, um einen fairen Preis für CO2-Emissionen importierter Produkte festzulegen. Die Übergangsphase des CBAM ist am 1. Oktober 2023 in Kraft getreten. Anfangs gilt der CBAM nur für ausgewählte Industrieprodukte und Vorprodukte, deren Produktion besonders kohlenstoffintensiv ist und die als besonders gefährdet für Carbon Leakage gelten. Sobald der CBAM vollständig aktiv ist, müssen alle importierenden Unternehmen die eingebetteten Emissionen für ihre Produkte deklarieren und die entsprechende Menge an CBAM-Zertifikaten abgeben. Es ist zu erwarten, dass importierende Unternehmen stark auf ihre internationalen Lieferanten angewiesen sein werden, um Informationen zu den eingebetteten Emissionen bereitstellen zu können. Indien ist sowohl ein wichtiger Handelspartner der EU als auch aufgrund seiner starken Abhängigkeit von Kohlekraftwerken ein siginifikanter Treibhausgasemittent. Importeure von Produkten aus Indien in die EU werden daher unter den CBAM-Vorschriften eine signifikante Anzahl von Kohlenstoffzertifikaten erwerben müssen und abgeben müssen. Dieser Artikel erklärt den funktionalen Mechanismus des CBAM und identifiziert die Produktströme von Indien in die EU für die betroffenen Produkte. Er beschreibt die Produktgruppen, ihre Bedeutung für indische Unternehmen sowie die zukünftigen Anforderungen und soll indischen Unternehmen, die in die Europäische Union exportieren, dabei helfen, sich auf die CBAM-Anforderungen sowohl während der Übergangsphase als auch bei vollständiger Inbetriebnahme des Systems vorzubereiten
Keywords: Q56; F13; Q58; F18; 330; Aluminium; CBAM; Carbon Border Adjustment Mechanism; Carbon Intensity; Emission Trading Scheme; EU-ETS; India; Imports; Iron & STeel